Significant lung volume reduction with endobronchial valves in a patient despite the presence of microcollaterals masked by low-flow Chartis phenotype - Yin, Yan; Hou, Gang; Herth, Felix; Wang, Xiao-bo; Wang, Qiu-yue; Kang, Jian (The International journal of chronic obstructive pulmonary disease, 2016)
Significant lung volume reduction with endobronchial valves in a patient despite the presence of microcollaterals masked by low-flow Chartis phenotype Yan Yin,1 Gang Hou,1 Felix J Herth,2 Xiao-bo Wang,1 Qiu-yue Wang,1 Jian Kang1 1Department of Respiratory Medicine, The First Hospital of China Medical University, Shenyang, People’s Republic of China; 2Department of Pneumology and Critical Care Medicine, Thoraxklinik, University of Heidelberg, Heidelberg, Germany Abstract: Satisfactory functional outcomes following bronchoscopic lung volume reduction (BLVR) using endobronchial valves (EBVs) depend on the absence of collateral ventilation (CV) between the target and adjunct lobes. The Chartis system has proven to be useful for determining whether CV is present or absent, but this system can also erroneously indicate the absence of CV, which can lead to BLVR failure. Here, we describe low-flow Chartis phenotype in the target lobe resulted in difficult judgment of existence of CV. Consequently, BLVR with EBVs implanted into the right upper bronchus failed to reduce lung volume or induce atelectasis. Inserting another EBV into the right middle bronchus blocked the latent CV, which led to significant lung volume reduction in the right upper lobe (RUL) and right middle lobe (RML) and to improve the pulmonary function, 6-min walking distance, and St George respiratory questionnaire scores over a 2-week follow-up period. Low flow in the target lobe is a unique Chartis phenotype and represents the uncertainty of CV, which is a risk factor for the failure of BLVR using EBVs. Clinicians should be aware of this possibility and might be able to resolve the problem by blocking the RUL and RML between which the CV occurs. Keywords: COPD, bronchoscopic lung volume reduction, collateral ventilation, endobronchial valves, Chartis assessment
Gesehen am 30.09.2021